Tracking the magmatic response to subduction initiation in the forearc mantle wedge: Insights from peridotite geochemistry of the Guleman and Kizildag ophiolites, Southeastern Turkey - Lin, Kuan-Yu; Wang, Kuo-Lung; Chung, Sun-Lin; Bingol, Ahmet Feyzi; Iizuka, Yoshiyuki; Lee, Hao-Yang (Elsevier, 2020)
The initiation of subduction is associated with sequential magmatic responses that lead to the formation of the forearc lithosphere, yet the detailed characteristics of these magmatic activities are not well constrained. Here we use mineral chemistries and bulk-rock trace-element contents of highly-depleted harzburgites from the Guleman and Kizildag ophiolites in Southeast Turkey to examine mantle wedge melting dynamics during subduction initiation. We focus on how different components from the subducting slabs potentially contribute to various stages of magmatism throughout the process. Mineral and bulk-rock compositions of these harzburgites are significantly different from those of abyssal peridotites, suggesting that our harzburgites cannot be explained as residues of anhydrous adiabatic melting and melt-rock interaction at mid-ocean ridges alone. This implies that the petrogenesis of SE Turkey harzburgites involves additional processes and components. Harzburgites with the most depleted heavy-rare earth element (HREE) contents are the ones with the highest abundance of strongly incompatible elements, which can be explained by open-system processes where the peridotites in the mantle wedge experienced melting and infiltration of enriched components simultaneously. Open-system dynamic melting models with continuous flux of sediment-derived melts can account for the observed correlation, but are numerically too low compared to the measured values. Based on the observed fractionation between Zr, Hf, and elements with similar incompatibility (middle REEs), we hypothesized the involvement of amphibolite-derived melt and modeled its numerical trace-element contents. Binary mixing between this hypothetical melt and residues of the former open-system model can coherently account for the majority of the obtained trace-element data. This indicates that magmatic events during subduction initiation likely involve multiple components and occur in multiple stages, and that melt-mantle interaction plays a significant role in oceanic forearc lithosphere formation. Based on our model, we suggest the high (Zr/MREE) N signatures in some boninites and depleted harzburgites found in modern forearcs and ophiolites could be inherited from amphibolite-derived melts. Moreover, the existence of slab melts agrees with current constraints on the reconstructed geothermal gradients during subduction initiation based on the petrology and geochemistry of metamorphic soles. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Tethyan SSZ ophiolites; Mantle peridotite trace-element geochemistry; Subduction initiation magmatism; Open-system melting